A COMPARATIVE ANALYSIS OF SERVICE CONVENIENCE BETWEEN MALE AND FEMALE AT PIZZA HUT MANADO TOWN SQUARE - Runtuwene, Liany .; Lapian, S.L.H.V. Joyce (Universitas Sam Ratulangi, 2019)
Abstract: The consumer convenience literature strong in certain respects, underdeveloped in other respects gives insufficient attention to service convenience. The prevailing pattern is either to treat service convenience generally or to lump services and goods together into an overall convenience construct. Consequently food consumption in Manado continues to increase, and increase consumer demand for fast food business. The aim of this research is to analyze service convenience between male and female of Pizza Hut Manado town measure by decision convenience, access convenience, transaction convenience and benefit convenience. This research is quantitative type of research, uses independent sample t-test as the analytical tool. The population of this research is peoples in Manado who has experience in Pizza Hut Manado Town Square, where the sample size is taken from 100. The result from this research found that there is no significant difference between male and female consumer of Pizza Hut Manado town square in access convenience and benefit convenience. Related with the findings there are recommendations for Pizza Hut that they can improve the quality of consumers’ waits for service.Keywords: comparative analysis, service convenience.